Desingning of the training process in regenerative microcycles for young skiers-racers - Taran L.N (Kharkov National Pedagogical University, 2012)
The purpose of the research consisted in development of basic provisions for creation of training programs in regenerative microcycles for young skiers-racers. In work was used the analysis of scientific and methodical literature, studying and generalization of practical experience of trainers, the analysis of documents of planning and the accounting of training process. Trainers took part in questioning in number of 19 people. It is established that long and tiresome loadings cause longer regenerative reactions from young athletes. The maintenance of regenerative microcycles is made by training occupations with small loadings on size. At an all-preparatory stage means of the general and special physical preparation use in relation 60 % and 40 %, and at a special-preparatory stage and in the competitive period ‒ 50 % and 50 % respectively.